Pengaruh Metode Pembelajaran Pohon Keluarga dalam Meningkatkan Hasil Belajar Pada Mata Pelajaran Sejarah - Destel Meri (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2019)
This study aims to determine the effect of applying the Family Tree method on student learning outcomes in learning History in class X SMAN 1 Payakumbuh District. This type of research is experimental quarsi research. The population in this study were all students of class X SMAN 1 District Payakumbuh consisting of 4 classes with the total number of students, namely 116 students. The sampling technique was taken by proportionate stratified random sampling. The result from the data analysis, it was obtained Thitung = 5.05 and T table = 1.68 where 1.68 <5.05> 1.68 which means that the hypothesis was accepted at the 95% confidence level. Thus it can be concluded that, there is the influence of the application of the Family Tree learning method to student learning outcomes compared to conventional learning methods in history learning in class X SMA N 1 Payakumbuh District. Keywords: Family Tree Method and Learning Outcomes